Pengaruh Jumlah Penduduk, Efisiensi Keuangan dan Biaya Barang dan Jasa terhadap Kondisi Keuangan Pemerintah Daerah: (Studi Empiris pada Pemerintah Provinsi di Indonesia Tahun 2020-2022) - Zuren, Latifah Annisa; Deviani (Universitas Negeri Padang, 2026)
This study aims to examine the effect of population, financial efficiency and cost of goods and services on the financial condition of local governments in Indonesia in the period 2020 to 2022. This study is a quantitative study. The type of data used is secondary data obtained from BPK and BPS throughout the provinces in Indonesia. The sample selection method in this study uses a purposive sampling method with a total sample of 32 provinces. Measurement of Financial Conditions is based on the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 19 of 2020. The data analysis used is multiple linear regression analysis, with the help of the SPSS 30 program. The results of the study show that population, financial efficiency and cost of goods and services have a significant positive effect on the financial condition of local governments